The effect of the speed and range of motion of movement on the hyperemic response to passive leg movement. Issue 8 (19th April 2019) - Gifford, Jayson R.; Bloomfield, Travis; Davis, Trevor; Addington, Amy; McMullin, Erin; Wallace, Taysom; Proffit, Meagan; Hanson, Brady
Abstract: Passive leg movement (PLM)‐induced hyperemia is used to assess the function of the vascular endothelium. This study sought to determine the impact of movement speed and range of motion (ROM) on the hyperemic response to PLM and determine if the currently recommended protocol of moving the leg through a 90° ROM at 180°/sec provides a peak hyperemic response to PLM. 11 healthy adults underwent multiple bouts of PLM, in which either movement speed (60–240°/sec) or ROM (30–120° knee flexion) were varied. Femoral artery blood flow (Doppler Ultrasound) and mean arterial pressure (MAP; photoplethysmography) were measured throughout. Movement speed generally exhibited positive linear relationships with the hyperemic response to PLM, eliciting 15–20% increase in hyperemia and conductance for each 30°/sec increase in speed ( P < 0.05). However, increasing the movement speed above 180°/sec was physically difficult and seemingly impractical to implement. ROM exhibited curvilinear relationships ( P <0.05) with hyperemia and conductance, which peaked at 90°, such that a 30° increase or decrease in ROM from 90° resulted in a 10–40% attenuation ( P < 0.05) in the hyperemic response. Alterations in the balance of antegrade and retrograde flow appear to play a role in this attenuation. Movement speed and ROM have a profound impact on PLM‐induced hyperemia. When using PLM to assess vascular endothelial function, it is recommended to perform the test at the traditional 180°/sec with 90° ROM, which offers a near peak hyperemic response, while maintaining test feasibility. Abstract : Passive leg movement‐induced hyperemia is a test to assessment peripheral endothelial function. In this study the impact of variation in test administration (i.e. speed at which the leg is moved and range of motion through which the leg is moved) were determined. Both movement speed and range of motion have profound effects on PLM‐induced hyperemia and should be tightly controlled.